ICT AND ONLINE STUDY METHODS IN TRADITIONAL FACE-TO-FACE STUDIES - Mickus, Artūras; Vidžiūnas, Antanas (Acta Paedagogica Vilnensia, 2009)
Intensive ICT implementation is one of the most important factors determining substantial changes in the field of university study environment over the last decade. This was influenced by computerization tendencies of all branches and modernization needs of universitiy study environment.Obviously, implementation of new expensive technologies requires to prepare new methods of studies and environment. Mostly these problems are analyzed under online studies context, where various technologies play the main role in organization of studies. The teacher is playing a supporting role to solve problems, which could not be solved by technological tools. Analyzing ICT implementation in traditional face-to-face studies, first of all the role of the teacher must be taken into account, who is the main knowledge resource and study organizer. Technologies are just supporting tools.The paper describes cost effectiveness and organizational problems of using ICT in face-to-face studies. A lot of resources were used to implement these technologies and online study methods in Lithuanian universities, but attention to cost effectiveness of these technologies isn’t sufficient. Therefore the main properties, advantages and disadvantages of different study models using ICT are discussed. Based on the experience of authors´ analysis of different support needs in studies are presented and means how to meet these needs are recommended. Another important problem discussed here is additional costs for supporting self studies and means for compensation of these costs.
Keywords: Information communication technology (ICT); online studies; face-to-face studies; cost effectiveness problems